Preparation method and application of nickel oxide-based target material
By spraying thermally conductive composite materials during vacuum hot pressing and sintering of nickel oxide targets, the problems of cracking and high resistivity of nickel oxide targets are solved, and higher relative density and yield rate are achieved, which improves its thermal conductivity and preparation. efficiency.
Patent Information
- Application Number
- CN202410875004.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-02
AI Technical Summary
Nickel oxide targets are prone to cracking during sintering, resulting in high resistivity and affecting their performance and application.
During vacuum hot press sintering, thermally conductive composite materials, including silica gel, nanotitanium dioxide, stearic acid, graphite and coupling agent, are sprayed to the blank to form a thermally conductive composite layer to reduce resistivity and prevent cracking.
It effectively reduces the resistivity of nickel oxide targets, improves its relative density and yield, and enhances thermal conductivity and preparation efficiency.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oxide target materials, and in particular to a preparation method and application of a nickel oxide-based target material. Background Art
[0002] In order to meet the needs of global energy economy and environmental protection, the development of perovskite solar cells is one of the most suitable options. The photoelectric conversion efficiency of perovskite solar cells has reached 25.5%, which meets the needs of the market. At present, high-performance PSCs are mainly based on the upright structure (nip). In order to further improve the photoelectric conversion efficiency (PCE) and stability of inverted PSCs, selecting appropriate electron and hole transport layers and optimizing the interface between the transport layer and the perovskite layer are one of the most effective solutions.
[0003] Nickel oxide, as a low-cost P-type semiconductor, is considered to be one of the most promising inorganic hole transport layers for inverted PSCs due to its wide band gap, high transmittance, matching work function, good chemical stability and excellent hole extraction efficiency.
[0004] Nickel oxide needs to be sintered during its preparation. Since nickel oxide has a variety of molecular formulas and the oxygen content of different molecular formulas is different, the target material will crack after sintering, and the cracked target material cannot be used anymore.
[0005] Therefore, how to effectively solve the problem of high resistivity and easy cracking of nickel oxide and improve the performance of nickel oxide has become an urgent problem to be solved. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present application provides a method for preparing and applying a nickel oxide-based target material.
[0007] In a first aspect, the present application provides a method for preparing a nickel oxide-based target material, using the following technical solution:
[0008] A method for preparing a nickel oxide-based target material, comprising the following steps:
[0009] Step 1, preparing a slurry of nickel oxide-based powder material, a dispersant, a binder and water, ball milling, and spray granulation to obtain particles;
[0010] Step 2: sieve the particles to obtain powder, and mold and press the powder to obtain a green body;
[0011] Step 3, after vacuum hot pressing and sintering, the green body is demoulded, cut, polished and trimmed to obtain a nickel oxide target;
[0012] Wherein, during the process of vacuum hot pressing and sintering of the green body, the thermally conductive composite material is sprayed onto the green body;
[0013] The thermally conductive composite material comprises the following raw material components in parts by weight:
[0014] 30-50 parts of silica gel, 20-30 parts of nano titanium dioxide, 5-10 parts of stearic acid, 7-16 parts of graphite, 5-15 parts of polyamide wax and 1-5 parts of coupling agent.
[0015] By adopting the above technical scheme, in the present application, during the process of vacuum hot pressing and sintering of the green body, the thermally conductive composite material is sprayed onto the green body, the thermally conductive composite material adheres to the surface of the green body, and penetrates into the green body under the action of high temperature and high pressure, and forms a composite layer on the surface of the green body, which can not only effectively prevent the target material from cracking, but also effectively improve the thermal conductivity of the target material. At the same time, the added thermally conductive composite material has certain lubricating properties, which effectively improves the preparation efficiency of the target material.
[0016] Preferably, the preparation steps of the thermally conductive composite material are as follows: mixing silica gel with stearic acid, adding ammonia water, adjusting the pH to 7, then adding nano titanium dioxide, graphite, and polyamide wax to mix, adding a coupling agent to mix, drying, and grinding to obtain a thermally conductive composite material.
[0017] By adopting the above technical scheme, the silica gel and stearic acid added in the present application are mixed to obtain a composite phase change material with thermal conductivity; the prepared composite phase change material reacts with nano-titanium dioxide, graphite, and polyamide wax under the action of a coupling agent, thereby preparing a thermally conductive composite material with thermal conductivity, anti-cracking performance, and lubrication performance.
[0018] Silica gel is added in the present application. The silica gel has a three-dimensional network structure. After the added silica is mixed with other raw materials, it is evenly dispersed under the action of a coupling agent and embedded in the silicon solution to form a thermally conductive composite material with thermal conductivity, anti-cracking performance, lubrication performance, and viscosity.
[0019] Preferably, the preparation method of silica gel comprises the following steps: mixing tetraethyl orthosilicate, ethanol and water, adding hydrochloric acid to adjust the pH to 3, and obtaining silica gel.
[0020] Preferably, the molar ratio of tetraethyl orthosilicate, ethanol and water is 1:4:(5-15).
[0021] Preferably, the temperature for mixing ethyl orthosilicate, ethanol and water is 50-70° C., and the mixing time is 20-40 minutes.
[0022] Preferably, the mixing time after adding the hydrochloric acid is 30-50 minutes.
[0023] Preferably, the steps of vacuum hot pressing sintering of the green body in step 3 are as follows: sinter the green body at a sintering temperature of 600-800°C and a vacuum degree of 0.08-0.1Mpa for 4-8 hours, spray the thermal conductive composite material into the heating furnace, raise the temperature to 1000°C-1500°C, maintain the vacuum degree at 0.05-0.1Mpa, introduce oxygen, and continue sintering for 5-12 hours.
[0024] Preferably, the spraying speed is 10-20 g / min.
[0025] In a second aspect, the present application provides a nickel oxide-based target material, which adopts the following technical solution:
[0026] A nickel oxide-based target material is prepared by the above preparation method.
[0027] In a third aspect, the present application provides an application of a nickel oxide-based target material in the preparation of a perovskite solar cell, using the following technical solution:
[0028] Application of a nickel oxide-based target material in the preparation of perovskite solar cells.
[0029] In summary, the present application includes at least one of the following beneficial technical effects:
[0030] The present application discloses a method for preparing and applying a nickel oxide-based target material. During the vacuum hot pressing and sintering process of the blank, a thermally conductive composite material is sprayed onto the blank. The thermally conductive composite material adheres to the surface of the blank, thereby effectively reducing the resistivity of the nickel oxide-based target material and improving the relative density and yield rate of the nickel oxide-based target material. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further illustrated by specific embodiments below. The specific embodiments do not limit the protection scope of the present invention; some non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the protection scope of the present invention.
[0032] The raw materials involved in this application are all commercially available products, among which:
[0033] Nickel oxide based powder material with a surface area of 7m 2 / g-10m 2 / g.
[0034] Dispersant, Zhongjing Oil CELUNAD-305, active ingredient content 40wt%, viscosity (25℃) 50cps;
[0035] Binder, analytical grade PVA produced by Sinopharm Chemical Reagent Co., Ltd.;
[0036] Nano-titanium dioxide was purchased from Jiangsu Tianxing New Materials Co., Ltd.;
[0037] Graphite was purchased from Yongshun Mineral Products Processing Plant in Lingshou County;
[0038] Polyamide wax, Troythix-150ACS, purchased from Troy Specialty Chemicals Trading (Shanghai) Co., Ltd.;
[0039] Coupling agent, coupling agent K550;
[0040] Tetraethyl orthosilicate was purchased from Tianjin Guangfu Fine Chemical Research Institute;
[0041] Stearic acid was purchased from Tianjin Bodi Chemical Co., Ltd.
[0042] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0043] Preparation Example 1:
[0044] Preparation of thermally conductive composite materials:
[0045] 1. Preparation of silica gel:
[0046] Tetraethyl orthosilicate, ethanol and water were added into a three-necked flask at a molar ratio of 1:4:10, and the three-necked flask was placed in a 60° C. water bath and stirred for 30 minutes. Hydrochloric acid was added to adjust the pH to 3, and the mixture was mixed for 40 minutes to obtain silica gel.
[0047] 2. Preparation of thermally conductive composite materials:
[0048] The raw material components of the thermal conductive composite material are as follows: 40 kg of silica gel, 25 kg of nano titanium dioxide, 8 kg of stearic acid, 11 kg of graphite, 10 kg of polyamide wax and 3 kg of coupling agent K550.
[0049] The preparation steps of the thermal conductive composite material are as follows: stir the silica gel, heat and melt the stearic acid, add the molten stearic acid to the silica sol, stir for 30 minutes, add ammonia water, adjust the pH to 7, stir for 20 minutes, add nano titanium dioxide, graphite, and polyamide wax and mix, add coupling agent K550 and mix, dry and grind the prepared mixture in a drying oven at 80°C to obtain a thermal conductive composite material.
[0050] Preparation Example 2:
[0051] Preparation of thermally conductive composite materials:
[0052] 1. Preparation of silica gel:
[0053] TEOS, ethanol and water were added into a three-necked flask at a molar ratio of 1:4:5, and the three-necked flask was placed in a 60° C. water bath and stirred for 30 minutes. Hydrochloric acid was added to adjust the pH to 3, and the mixture was mixed for 40 minutes to obtain silica gel.
[0054] 2. Preparation of thermally conductive composite materials:
[0055] The raw material components of the thermal conductive composite material are as follows: 30 kg of silica gel, 20 kg of nano titanium dioxide, 5 kg of stearic acid, 7 kg of graphite, 5 kg of polyamide wax and 1 kg of coupling agent K550.
[0056] The preparation steps of the thermal conductive composite material are as follows: stir the silica gel, heat and melt the stearic acid, add the molten stearic acid to the silica sol, stir for 30 minutes, add ammonia water, adjust the pH to 7, stir for 20 minutes, add nano titanium dioxide, graphite, and polyamide wax and mix, add coupling agent K550 and mix, dry and grind the prepared mixture in a drying oven at 80°C to obtain a thermal conductive composite material.
[0057] Preparation Example 3:
[0058] Preparation of thermally conductive composite materials:
[0059] 1. Preparation of silica gel:
[0060] TEOS, ethanol and water were added into a three-necked flask at a molar ratio of 1:4:15. The three-necked flask was placed in a 60° C. water bath and stirred for 30 minutes. Hydrochloric acid was added to adjust the pH to 3. The mixture was mixed for 40 minutes to obtain silica gel.
[0061] 2. Preparation of thermally conductive composite materials:
[0062] The raw material components of the thermal conductive composite material are as follows: 50 kg of silica gel, 30 kg of nano titanium dioxide, 10 kg of stearic acid, 16 kg of graphite, 15 kg of polyamide wax and 5 kg of coupling agent K550.
[0063] The preparation steps of the thermal conductive composite material are as follows: stir the silica gel, heat and melt the stearic acid, add the molten stearic acid to the silica sol, stir for 30 minutes, add ammonia water, adjust the pH to 7, stir for 20 minutes, add nano titanium dioxide, graphite, and polyamide wax to mix, add coupling agent K550 to mix, and then dry and grind the prepared mixture in a drying oven at 80°C to obtain a thermal conductive composite material. Embodiment 1:
[0064] A method for preparing a nickel oxide-based target material, comprising the following steps:
[0065] Step 1, weighing nickel oxide-based powder material, dispersant, binder and water to mix to form a slurry, grinding each raw material with a zirconium oxide ball for 8 hours until the D50 of the slurry is less than 250nm and the D90 is less than 500nm, and then spraying the obtained slurry to obtain spherical nickel oxide-based particles with a D50 of less than 25μm and a D90 of less than 48μm;
[0066] Among them, the nickel oxide-based powder material is nickel oxide powder, accounting for 20%; zirconium oxide balls for ball milling (particle size of 0.5mm) account for 50%, deionized water accounts for 28%, dispersant accounts for 0.5%, and binder accounts for 1.5%;
[0067] Step 2, sieving the particles to obtain powder, filling the powder into a mold, and pressing the powder under 0.35 MPa to obtain a green body;
[0068] Step 3, vacuum hot pressing sintering: sinter the green body at a sintering temperature of 700°C and a vacuum degree of 0.09 MPa for 6 hours, spray the thermal conductive composite material into the heating furnace, raise the temperature to 1300°C, maintain the vacuum degree at 0.08 MPa, introduce oxygen, and continue sintering for 8 hours; wherein, the spraying speed is 15 g / min.
[0069] Step 4: demolding, cutting, grinding and trimming the green body after vacuum hot pressing sintering to obtain a nickel oxide target.
[0070] The thermally conductive composite material is prepared according to Preparation Example 1. Embodiment 2:
[0071] A method for preparing a nickel oxide-based target material, comprising the following steps:
[0072] Step 1, weighing nickel oxide-based powder material, dispersant, binder and water to mix to form a slurry, grinding each raw material with a zirconium oxide ball for 8 hours until the D50 of the slurry is less than 250nm and the D90 is less than 500nm, and then spraying the obtained slurry to obtain spherical nickel oxide-based particles with a D50 of less than 25μm and a D90 of less than 48μm;
[0073] Among them, the nickel oxide-based powder material is nickel oxide powder, accounting for 20%; zirconium oxide balls for ball milling (particle size of 0.5mm) account for 50%, deionized water accounts for 28%, dispersant accounts for 0.5%, and binder accounts for 1.5%;
[0074] Step 2, sieving the particles to obtain powder, filling the powder into a mold, and pressing the powder under 0.35 MPa to obtain a green body;
[0075] Step 3, vacuum hot pressing sintering: sinter the green body at a sintering temperature of 600°C and a vacuum degree of 0.08Mpa for 4 hours, spray the thermal conductive composite material into the heating furnace, raise the temperature to 1000°C, maintain the vacuum degree at 0.05Mpa, introduce oxygen, and continue sintering for 5 hours; wherein, the spraying speed is 15g / min.
[0076] Step 4: demolding, cutting, grinding and trimming the green body after vacuum hot pressing sintering to obtain a nickel oxide target.
[0077] The thermally conductive composite material is prepared according to Preparation Example 2. Embodiment 3:
[0078] A method for preparing a nickel oxide-based target material, comprising the following steps:
[0079] Step 1, weighing nickel oxide-based powder material, dispersant, binder and water to mix to form a slurry, grinding each raw material with a zirconium oxide ball for 8 hours until the D50 of the slurry is less than 250nm and the D90 is less than 500nm, and then spraying the obtained slurry to obtain spherical nickel oxide-based particles with a D50 of less than 25μm and a D90 of less than 48μm;
[0080] Among them, the nickel oxide-based powder material is nickel oxide powder, accounting for 20%; zirconium oxide balls for ball milling (particle size of 0.5mm) account for 50%, deionized water accounts for 28%, dispersant accounts for 0.5%, and binder accounts for 1.5%;
[0081] Step 2, sieving the particles to obtain powder, filling the powder into a mold, and pressing the powder under 0.35 MPa to obtain a green body;
[0082] Step 3, vacuum hot pressing sintering: sinter the green body at a sintering temperature of 800°C and a vacuum degree of 0.1 MPa for 8 hours, spray the thermal conductive composite material into the heating furnace, raise the temperature to 1500°C, maintain the vacuum degree at 0.1 MPa, introduce oxygen, and continue sintering for 12 hours; wherein, the spraying speed is 20 g / min.
[0083] Step 4: demolding, cutting, grinding and trimming the green body after vacuum hot pressing sintering to obtain a nickel oxide target.
[0084] The thermally conductive composite material is prepared according to Preparation Example 3. Embodiment 4:
[0085] A method for preparing a nickel oxide-based target material, comprising the following steps:
[0086] Step 1, weighing nickel oxide-based powder material, dispersant, binder and water to mix to form a slurry, grinding each raw material with a zirconium oxide ball for 8 hours until the D50 of the slurry is less than 250nm and the D90 is less than 500nm, and then spraying the obtained slurry to obtain spherical nickel oxide-based particles with a D50 of less than 25μm and a D90 of less than 48μm;
[0087] Among them, the nickel oxide-based powder material is nickel oxide powder, accounting for 20%; zirconium oxide balls for ball milling (particle size of 0.5mm) account for 50%, deionized water accounts for 28%, dispersant accounts for 0.5%, and binder accounts for 1.5%;
[0088] Step 2, sieving the particles to obtain powder, filling the powder into a mold, and pressing the powder under 0.35 MPa to obtain a green body;
[0089] Step 3, vacuum hot pressing sintering: sinter the green body at a sintering temperature of 700°C and a vacuum degree of 0.09 MPa for 6 hours, spray the thermal conductive composite material into the heating furnace, raise the temperature to 1300°C, maintain the vacuum degree at 0.08 MPa, introduce oxygen, and continue sintering for 8 hours; wherein, the spraying speed is 15 g / min.
[0090] Step 4: demolding, cutting, grinding and trimming the green body after vacuum hot pressing sintering to obtain a nickel oxide target.
[0091] The thermally conductive composite material is prepared according to Preparation Example 2. Embodiment 5:
[0092] A method for preparing a nickel oxide-based target material, comprising the following steps:
[0093] Step 1, weighing nickel oxide-based powder material, dispersant, binder and water to mix to form a slurry, grinding each raw material with a zirconium oxide ball for 8 hours until the D50 of the slurry is less than 250nm and the D90 is less than 500nm, and then spraying the obtained slurry to obtain spherical nickel oxide-based particles with a D50 of less than 25μm and a D90 of less than 48μm;
[0094] Among them, the nickel oxide-based powder material is nickel oxide powder, accounting for 20%; zirconium oxide balls for ball milling (particle size of 0.5mm) account for 50%, deionized water accounts for 28%, dispersant accounts for 0.5%, and binder accounts for 1.5%;
[0095] Step 2, sieving the particles to obtain powder, filling the powder into a mold, and pressing the powder under 0.35 MPa to obtain a green body;
[0096] Step 3, vacuum hot pressing sintering: sinter the green body at a sintering temperature of 700°C and a vacuum degree of 0.09 MPa for 6 hours, spray the thermal conductive composite material into the heating furnace, raise the temperature to 1300°C, maintain the vacuum degree at 0.08 MPa, introduce oxygen, and continue sintering for 8 hours; wherein, the spraying speed is 15 g / min.
[0097] Step 4: demolding, cutting, grinding and trimming the green body after vacuum hot pressing sintering to obtain a nickel oxide target.
[0098] The thermally conductive composite material is prepared according to Preparation Example 3. Embodiment 6:
[0099] The difference from Example 1 is that when preparing the thermally conductive composite material, 30 kg of silica gel is added. Embodiment 7:
[0100] The difference from Example 1 is that when preparing the thermally conductive composite material, 50 kg of silica gel is added. Embodiment 8:
[0101] The difference from Example 1 is that when preparing the thermally conductive composite material, 5 kg of stearic acid is added. Embodiment 9:
[0102] The difference from Example 1 is that when preparing the thermally conductive composite material, 10 kg of stearic acid is added.
[0103] Comparative Example 1:
[0104] The difference from Example 1 is that during the vacuum hot pressing sintering process, the thermal conductive composite material is not sprayed.
[0105] Comparative Example 2:
[0106] The difference from Example 1 is that when preparing the thermally conductive composite material, no silicon dioxide gel is added.
[0107] Comparative Example 3:
[0108] The difference from Example 1 is that when preparing the thermally conductive composite material, no nano titanium dioxide is added.
[0109] Comparative Example 4:
[0110] The difference from Example 1 is that stearic acid is not added when preparing the thermally conductive composite material.
[0111] Comparative Example 5:
[0112] The difference from Example 1 is that no graphite is added when preparing the thermally conductive composite material.
[0113] Comparative Example 6:
[0114] The difference from Example 1 is that when preparing the thermally conductive composite material, 29 kg of silica gel is added.
[0115] Comparative Example 7:
[0116] The difference from Example 1 is that when preparing the thermally conductive composite material, 51 kg of silica gel is added.
[0117] Comparative Example 8:
[0118] The difference from Example 1 is that when preparing the thermally conductive composite material, 4 kg of stearic acid is added.
[0119] Comparative Example 9:
[0120] The difference from Example 1 is that when preparing the thermally conductive composite material, 11 kg of stearic acid is added.
[0121] Performance testing:
[0122] The following performance tests were performed on the nickel oxide targets provided in Examples 1-9 and Comparative Examples 1-9:
[0123] Resistivity: The resistivity of nickel oxide target is tested according to GB / T40007-2021.
[0124] Relative density: The relative density of nickel oxide target was measured by Archimedes method.
[0125] Yield rate: 50 nickel oxide target samples were prepared in each embodiment and comparative example, and the surface of each nickel oxide target sample was observed to see whether there were cracks. The sample without cracks was a good product, and the yield rate = number of good products ÷ 50 × 100%.
[0126] Table 1 Performance test results of nickel oxide target
[0127]
[0128] It can be seen from Table 1 that the nickel oxide target prepared by the method of Examples 1-9 has lower resistivity, higher relative density and higher yield.
[0129] Combining Example 1 and Comparative Example 1, it can be seen that the resistivity, relative density and yield rate of Example 1 are better than those of Comparative Example 1, indicating that during the vacuum hot pressing sintering process, spraying the thermally conductive composite material and coating the surface of the nickel oxide target with the thermally conductive composite material can effectively reduce the resistivity of the nickel oxide target and reduce the cracking of the nickel oxide target.
[0130] Combining Example 1 and Comparative Example 2, it can be seen that the resistivity, relative density and yield rate of Example 1 are better than those of Comparative Example 2, indicating that the addition of silica gel can react with other raw materials to generate a thermally conductive composite material with certain thermal conductivity, and the added thermally conductive composite material can adhere to the surface of the nickel oxide target, thereby effectively reducing the resistivity of the nickel oxide target and reducing the cracking of the nickel oxide target.
[0131] Combining Example 1 and Comparative Example 3, it can be seen that the resistivity, relative density and yield rate of Example 1 are better than those of Comparative Example 3, indicating that the addition of nano-titanium dioxide can react with other raw materials to generate a thermally conductive composite material with thermal conductivity. The added thermally conductive composite material can adhere to the surface of the nickel oxide target, which can effectively reduce the resistivity of the nickel oxide target and reduce the cracking of the nickel oxide target.
[0132] Combining Example 1 and Comparative Example 4, it can be seen that the resistivity, relative density and yield rate of Example 1 are better than those of Comparative Example 4, indicating that stearic acid is added and the added stearic acid is mixed with silica gel to prepare a phase change material with thermal conductivity, thereby preparing a thermally conductive composite material with thermal conductivity, and the added thermally conductive composite material can adhere to the surface of the nickel oxide target, further reducing the resistivity of the nickel oxide target and reducing the cracking of the nickel oxide target.
[0133] Combining Example 1 and Comparative Example 5, it can be seen that the resistivity, relative density and yield rate of Example 1 are better than those of Comparative Example 5, indicating that the addition of graphite can react with other raw materials to generate a thermally conductive composite material with thermal conductivity. The added thermally conductive composite material can adhere to the surface of the nickel oxide target, thereby improving the thermal conductivity of the nickel oxide target, reducing the resistivity of the nickel oxide target, and reducing the cracking of the nickel oxide target.
[0134] Combining Example 1, Example 6, Example 7, Comparative Example 6 and Comparative Example 7, it can be seen that the amount of silica gel added has an impact on the performance of the nickel oxide target, and when the amount of silica gel added is 30-50kg, the performance of the nickel oxide target is optimal.
[0135] Combining Example 1, Example 8, Example 9, Comparative Example 8 and Comparative Example 9, it can be seen that the amount of stearic acid added has an effect on the performance of the nickel oxide target, and when the amount of stearic acid added is 5-10 kg, the performance of the nickel oxide target is optimal.
Claims
1. A method for preparing a nickel oxide-based target material, It is characterized in that Here are the steps: Step 1, preparing a slurry of nickel oxide-based powder material, a dispersant, a binder and water, ball milling, and spray granulation to obtain particles; Step 2, sieving the particles to obtain powder, and molding and pressing the powder to obtain a green body; Step 3, after vacuum hot pressing and sintering, the green body is demoulded, cut, polished and trimmed to obtain a nickel oxide target; Wherein, during the vacuum hot pressing sintering process of the green body, the thermally conductive composite material is sprayed onto the green body; The thermally conductive composite material comprises the following raw material components in parts by weight: 30-50 parts of silica gel, 20-30 parts of nano titanium dioxide, 5-10 parts of stearic acid, 7-16 parts of graphite, 5-15 parts of polyamide wax and 1-5 parts of coupling agent.
2. The method for preparing a nickel oxide-based target material according to claim 1, It is characterized in that The preparation steps of the thermal conductive composite material are as follows: mixing silica gel with stearic acid, adding ammonia water, adjusting the pH to 7, adding nano titanium dioxide, graphite, and polyamide wax, mixing, adding a coupling agent, mixing, drying, and grinding to obtain a thermal conductive composite material.
3. The method for preparing a nickel oxide-based target material according to claim 1, It is characterized in that The preparation method of silica gel comprises the following steps: mixing ethyl orthosilicate, ethanol and water, adding hydrochloric acid to adjust the pH to 3, and obtaining silica gel.
4. The method for preparing a nickel oxide-based target material according to claim 3, Features: The molar ratio of tetraethyl orthosilicate, ethanol and water is 1:4:(5-15).
5. The method for preparing a nickel oxide-based target material according to claim 3, Features: The temperature for adding ethyl orthosilicate, ethanol and water for mixing is 50-70° C. and the mixing time is 20-40 minutes.
6. The method for preparing a nickel oxide-based target material according to claim 3, Features: The mixing time after adding the hydrochloric acid is 30-50 minutes.
7. The method for preparing a nickel oxide-based target material according to claim 1, It is characterized in that The steps of vacuum hot pressing sintering of the green body in step 3 are as follows: sinter the green body at a sintering temperature of 600-800°C and a vacuum degree of 0.08-0.1MPa for 4-8h, spray the thermal conductive composite material into the heating furnace, raise the temperature to 1000°C-1500°C, maintain the vacuum degree at 0.05-0.1MPa, introduce oxygen, and continue sintering for 5-12h.
8. The method for preparing a nickel oxide-based target material according to claim 7, Features: The spraying speed is 10-20g / min.
9. A nickel oxide-based target material, It is characterized in that The nickel oxide-based target is prepared by the preparation method described in any one of claims 1-8.
10. Use of the nickel oxide-based target material as claimed in claim 9 in the preparation of perovskite solar cells.
